The Learning Model of Information Processing in Building Islamic Characters at State Senior High Schools in East Lombok - Enti, Enti; Khairani, Khairani (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research was aimed to know the implementation of information processing learning model in building student's islamic charactera at state senior high schools in East Lombok. East lombok is very famous of its iconic destination of thousand mosques. Its islamic nature become the reason of the development of Islmac education in high schools in East Lombok. The purpose of this reswarch was two discuss the strengths of information processing learning model in building student's islamic characters. It was a qualitative research, using a descriptive approach. To collect the data, field observation and interview with sources about the model information were conducted. The result of this research is expected to give a description of the model implementation at state senior high schools in East Lombok.